Audiovisual language in social networks in Iberoamerica: A Systematic review of the literature between 2012 and 2022 (LACCEI, 2024)
The accelerated technological development and the emergence of new digital platforms have given way to new ways of communication. Audiovisual language plays a very important role in social networks, which with their different styles invade the internet with audiovisual content that has the power to transmit a message quickly and easily. Based on this, the objective of determining the trend of audiovisual language studies in social networks in Latin America was established. The method has been a systematic review of the literature of 31 articles published between 2012 and 2022 in the Ebsco, ProQuest, ScienceDirect and Scopus databases. The validation followed the inclusion and exclusion criteria, identification of the databases, search engines and evaluation and description of the results. The findings indicate that the audiovisual language in social networks has made it possible to materialize the reality and the point of view of the viewers, thus becoming a conceptualization tool for the production of audiovisual content. Likewise, it is concluded that there is a predominance of social networks due to the use of audiovisual language with the purpose of producing content that better transmits a message and impacts viewers.